A Case Series of Persistent SARS-CoV-2 Infection in Immunocompromised Pediatric Patients - Mohamed Y. Ahmed; Jane B. Taylor; Rajesh K. Aneja; Qian Wang; John V. Williams (Case Reports in Critical Care)
Diagnosis and management of SARS-CoV-2 infection in immunocompromised patients are extremely challenging. These patients can have atypical clinical courses, and there is a paucity of data regarding clinical features, diagnostic findings, and the safety and efficacy of available therapeutic agents used to treat COVID-19 in these patients. In this case series, we report atypical COVID-19 presentations in 4 immunocompromised pediatric patients who were admitted with acute respiratory failure after an initial diagnosis of COVID-19 a few weeks earlier. All patients included in this cohort showed persistent worsening respiratory symptoms for several weeks before hospital presentation. While they manifested common COVID-19 sequelae, they also had rare COVID-19-related pathognomonic and radiographic features developed along their hospital course. Multiple therapeutic agents were used in their COVID-19 management, including corticosteroids, remdesivir, and monoclonal antibodies. All three patients who have received concurrent therapy with remdesivir, hydrocortisone, and monoclonal antibodies survived, and only one patient died as a direct complication of COVID-19 ARDS with secondary pulmonary mucormycosis. Our outcomes suggest the potential benefit of remdesivir use in combination with hydrocortisone and monoclonal antibodies in the management of severe COVID-19 ARDS in this group, as well as the importance of close surveillance and early administration of broad empirical antimicrobial and antifungal coverage if clinically indicated in this high-risk population.